CHUVASH DIASPORA OF KAZAKHSTAN IN THE SECOND HALF OF THE XX – THE FIRST QUARTER OF THE XXI CENTURIES: FORMATION, REMIGRATION PROCESSES, CURRENT STATE - Egorova, Oksana; Vyazova, Olga; Dmitrieva, Inga; Petrov, Nikolai; Chibis, Aleksandr (Revista Inclusiones, 2020)
The relevance of the problem being investigated is due to the steady tendency of reduction the number of Chuvash in the territory of modern Kazakhstan. The purpose of the article is to consider the process of formation of the Chuvash diaspora in Kazakhstan during the Soviet period, and to study the causes of its decrease in modern conditions, primarily due to re-emigration. The leading approach to the study of this problem is a comprehensive analysis of published sources and field material. The article uses methods of quantitative analysis, cartographic method, oral-historical method. The main result was an analysis of the dynamics of the number of Chuvash people in Kazakhstan. The materials of the article may be useful for ethnographers, sociologists, and other scientists as a reserve for further study of the processes occurring within the national diasporas in the territory of states that were formerly a part of the USSR.